Injectable nanofiber-reinforced bone cement with controlled biodegradability for minimally-invasive bone regeneration - Peihao Cai; Shunyi Lu; Jieqin Yu; Lan Xiao; Jiayi Wang; Haifeng Liang; Lei Huang; Guanjie Han; Mengxuan Bian; Shihao Zhang; Jian Zhang; Changsheng Liu; et al. (Bioactive Materials, 2023)
Injectable materials show their special merits in regeneration of damaged/degenerated bones in minimally-invasive approach. Injectable calcium phosphate bone cement (CPC) has attracted broad attention for its bioactivity, as compared to non-degradable polymethyl methacrylate cement. However, its brittleness, poor anti-washout property and uncontrollable biodegradability are the main challenges to limit its further clinical application mainly because of its stone-like dense structure and fragile inorganic-salt weakness. Herein, we developed a kind of injectable CPC bone cement with porous structure and improved robustness by incorporating poly(lactide-co-glycolic acid) (PLGA) nanofiber into CPC, with carboxymethyl cellulose (CMC) to offer good injectability as well as anti-wash-out capacity. Furthermore, the introduction of PLGA and CMC also enabled a formation of initial porous structure in the cements, where PLGA nanofiber endowed the cement with a dynamically controllable biodegradability which provided room for cell movement and bone ingrowth. Interestingly, the reinforced biodegradable cement afforded a sustainable provision of Ca2+ bioactive components, together with its porous structure, to improve synergistically new bone formation and osteo-integration in vivo by using a rat model of femur condyle defect. Further study on regenerative mechanisms indicated that the good minimally-invasive bone regeneration may come from the synergistic enhanced osteogenic effect of calcium ion enrichment and the improved revascularization capacity contributed from the porosity as well as the lactic acid released from PLGA nanofiber. These results indicate the injectable bone cement with high strength, anti-washout property and controllable biodegradability is a promising candidate for bone regeneration in a minimally-invasive approach.